Research led by participants: a new social contract for a new kind of research. Issue 4 (30th March 2015) - Vayena, Effy; Brownsword, Roger; Edwards, Sarah Jane; Greshake, Bastian; Kahn, Jeffrey P; Ladher, Navjoyt; Montgomery, Jonathan; O'Connor, Daniel; O'Neill, Onora; Richards, Martin P; Rid, Annette; Sheehan, Mark; et al.
Abstract : In recent years, there have been prominent calls for a new social contract that accords a more central role to citizens in health research. Typically, this has been understood as citizens and patients having a greater voice and role within the standard research enterprise. Beyond this, however, it is important that the renegotiated contract specifically addresses the oversight of a new, path-breaking approach to health research: participant-led research. In light of the momentum behind participant-led research and its potential to advance health knowledge by challenging and complementing traditional research, it is vital for all stakeholders to work together in securing the conditions that will enable it to flourish.